1989
DOI: 10.1557/proc-170-123
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Water on the Epoxy-Resin-Glass Interphases

Abstract: The absorption of water in glass fiber reinforced epoxy resins is a complex process. With dynamic-mechanical measurements it is possible to distinguish locations of water in the resin-glass interphase, in micro-cracks of the resin, and diluted in the bulk polymer. The dominant mechanism of incorporation depends on the resin/hardener system, the surface treatment of the glass fabrics, and the sorption temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Papanicolaou and Pappa [13] further found that, although plasticization caused an increase in the value of the loss tangent, the formation of microcavities due to accelerated deterioration through immersion at higher temperatures resulted in a decrease in tan due to changes in morphology, which again can be seen in Table 2 and can be correlated with irreversible damage, especially at the higher temperature levels in the form of matrix-crack coalescence, microvoid formation and growth, fiber-matrix debonding, and even fiber level degradation (as seen in Figure 4(c)). A further examination of Table 2 shows that the value of tan increases for a given time of immersion with the temperature of immersion, which follows earlier results reported by Papanicolaou and Pappa [13], and Marzi et al [25].…”
Section: Resultssupporting
confidence: 88%
“…Papanicolaou and Pappa [13] further found that, although plasticization caused an increase in the value of the loss tangent, the formation of microcavities due to accelerated deterioration through immersion at higher temperatures resulted in a decrease in tan due to changes in morphology, which again can be seen in Table 2 and can be correlated with irreversible damage, especially at the higher temperature levels in the form of matrix-crack coalescence, microvoid formation and growth, fiber-matrix debonding, and even fiber level degradation (as seen in Figure 4(c)). A further examination of Table 2 shows that the value of tan increases for a given time of immersion with the temperature of immersion, which follows earlier results reported by Papanicolaou and Pappa [13], and Marzi et al [25].…”
Section: Resultssupporting
confidence: 88%
“…Various aspects of the phenomenon of moisture absorption in polymer composites and its effect on their mechanical properties have been reported by many scientists 4–7. Detailed studies on the kinetics of water sorption and influence of water on the interphases in plastics and rubber composites have been reported 8–10. Sapieha et al11 investigated the swelling of cellulosic fibers in composites and showed that water sorption is a complex phenomenon that requires in‐depth study.…”
Section: Introductionmentioning
confidence: 99%